2022
DOI: 10.1080/21655979.2022.2063648
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA00978 contributes to growth and metastasis of hepatocellular carcinoma cells via mediating microRNA-125b-5p/SOX12 pathway

Abstract: As a malignant tumor, HCC (hepatocellular carcinoma) is featured by a high recurrence rate with a poor prognosis. Increasing evidence supports an important role of lincRNAs in HCC. Here, the purpose of the study was to explore the function of LINC00978 (long non-coding RNA00978) in HCC and the underlying mechanisms. LINC00978 expression and its association with the progression of HCC were analyzed using HCC TCGA datasets. LINC00978 expression in tissues was measured using real-time PCR. Then, we knocked down L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, LINC00978 silencing could inhibit the development and metastasis of HCC cells. It was discovered that LINC00978 could sponge microRNA-125b-5p and that SOX12 (SRY-Box Transcription Factor 12) was one of its direct target genes (Cheng et al, 2022). In fact, LINC00978 has been recommended as a fundamental player in HCC diagnosis, prognosis, and future therapeutic options/targets.…”
Section: Lncrnas Involved In Hcc Diagnosis and Prognosismentioning
confidence: 99%
“…Furthermore, LINC00978 silencing could inhibit the development and metastasis of HCC cells. It was discovered that LINC00978 could sponge microRNA-125b-5p and that SOX12 (SRY-Box Transcription Factor 12) was one of its direct target genes (Cheng et al, 2022). In fact, LINC00978 has been recommended as a fundamental player in HCC diagnosis, prognosis, and future therapeutic options/targets.…”
Section: Lncrnas Involved In Hcc Diagnosis and Prognosismentioning
confidence: 99%
“…Studies suggest that MIR4435-2HG exhibits a significant increase in hepatocellular carcinoma tissues compared to adjacent normal tissues and shows a positive correlation with tumor size, metastasis, and unfavorable prognosis, and can be used as a prognostic biomarker [64]. Additionally, studies have found that silencing MIR4435-2HG inhibits the migration ability and EMT process induced by hepatic stellate cells in hepatocellular carcinoma cells [14,27,28]. Transcriptomics analysis revealed a substantial increase in the relative expression of MIR4435-2HG in hepatocellular carcinoma cohorts when compared to non-hepatocellular carcinoma and healthy control cohorts.…”
Section: Mir4435-2hg and Hepatocellular Carcinomamentioning
confidence: 99%
“…Current research shows that MIR4435-2HG can sequester miR-138-5p, upregulating SOX4, thereby promoting the growth, migration, and EMT process of gastric cancer cells [26]. In hepatocellular carcinoma, MIR4435-2HG sequesters miR-1-3p, miR-125b-5p, miR-22-3p, miR-513a-5p and miR-136-5p, upregulating downstream target genes such as MM9, SRY-Box transcription factor 12 (SOX12), Ribonucleotide reductase M1/2 subunit (RRM1/2), Tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ), Kruppel like factor 5 (KLF5), and B3GNT, thereby promoting hepatocellular carcinoma progression [13,27,28,52,[104][105][106][107]. Additionally, MIR4435-2HG is associated with the upregulation of specific miRNAs, such as the promotion of hepatocellular carcinoma cell proliferation through the upregulation of miRNA-487a [14].…”
Section: Competitive Endogenous Rnasmentioning
confidence: 99%
“…Individuals with HCC have shown aberrant miRNA levels in multiple studies. Because of their robust presence in body tissues and fluids and easy detectability [16], miRNA expression is not only used as a biomarker for diagnosis and metastasis but also predicts therapeutic response, recurrence, and overall HCC survival rate [17][18][19][20]. Research has proven that METTL1 can regulate microRNAs in an m 7 G-dependent pattern.…”
Section: Introductionmentioning
confidence: 99%